Assembling Victory: Defense Industries Limited, Ajax, 1941-1945 - Tubb, Lisa (Ontario History, 2019)
Located approximately forty kilometres outside of Toronto, Defense Industries Limited (DIL) established one of the largest wartime factories not only in Canada, but also the British Empire, in 1941. For ‘bomb girl’ Louise Johnson, a worker at DIL, her role and impact in the war machine was quite clear: “We knew our importance. If the boys didn’t have shells, they couldn’t win the war.” This paper explores the experience of working in a munitions factory through a case study of Defense Industries Limited in Ajax, Ontario. This study will contribute to a wider understanding of home front service and sacrifice, by shedding light on local, micro-level histories, and on the individuals who contributed greatly to Canada’s munitions production during the Second World War.